2001
DOI: 10.1046/j.1439-0418.2001.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of sulphur compounds for breeding success of Ips typographus L. (Col., Scolytidae) on Norway Spruce (Picea abies [L.] Karst.)

Abstract: Bark beetles, especially Ips typographus L. represent a severe biotic threat for spruce (Picea abies [L.] Karst.) at low altitudes in Europe. We compared sulphur (total S, SO42−, glutathione, cysteine, methionine), nitrogen (total N, NO3−, total protein, free amino acids), carbon, total phosphorus and PO43−, tree vigour index (TVI) and water content of the phloem after felling, and their dependent changes (tdc) with the breeding success of I. typographus. Twenty trees were classified according to age (34/90 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Besides that, tree’s phloem, the main feed source for the beetle, has been described as a sugar-rich source but poor in phosphorus, nitrogen, and vitamins, among other relevant nutrients [ 7 , 8 , 9 ], and it has been suggested that the provision of these scarce substances could be a role of the beetle microbiota [ 1 ]. Phosphorus and nitrogen are essential nutrients for live development.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, tree’s phloem, the main feed source for the beetle, has been described as a sugar-rich source but poor in phosphorus, nitrogen, and vitamins, among other relevant nutrients [ 7 , 8 , 9 ], and it has been suggested that the provision of these scarce substances could be a role of the beetle microbiota [ 1 ]. Phosphorus and nitrogen are essential nutrients for live development.…”
Section: Introductionmentioning
confidence: 99%
“…GSH content was high in phloem tissues from spruce bark showing low breeding success of bark beetles. Low GSH contents were found in phloem tissues of trees with high insect breeding success (Mattanovich et al, 2001). However, these data do not distinguish between the predisposition of spruce and the consequence of insect attack.…”
Section: ±mentioning
confidence: 79%
“…ships. Only one study with trees has been published which investigated the relationship between S and insect attack (Mattanovich et al, 2001). GSH content was high in phloem tissues from spruce bark showing low breeding success of bark beetles.…”
Section: ±mentioning
confidence: 99%
“…Highly reduced sulfur contents in acorns are translated directly to a high cysteine status of feeding mites . Furthermore, it has been hypothesized that reduced sulfur compounds in the bark are a determinant for the breeding success of bark beetles, but a clear connection has not been established, as yet (Mattanovich et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being the most abundant water-soluble antioxidant in plant cells (Smirnoff and Wheeler, 2000), ascorbate is also required for the re-conversion of SA • to SA yielding monodehydroascorbate, since ascorbate is highly reactive against phenoxyl radicals generated by peroxidases during oxidative stress (Kawano and Muto, 2000). Until now only a few investigations have dealt with antioxidative systems in bark beetle affected Norway spruce (Mattanovich et al, 2001;Pučko et al, 2005), although antioxidative defence systems have often been used as stress indicators for the diagnosis of disturbances in forest trees (Tausz et al, , 2004Tausz, 2007;Herbinger et al, 2005;Hofer et al, 2008). In previous work (Urbanek Krajnc, 2009), a temporal analysis of antioxidant contents in the phloem tissue of Norway spruce was performed when the bark was exposed to increasing levels of bark beetle attack.…”
Section: Introductionmentioning
confidence: 99%